Recurring subacute thyroiditis after SARS-CoV-2 mRNA vaccine: A case report - Vasiliki Vasileiou; Stavroula A. Paschou; Xakousti Tzamali; Marina Mitropoulou; Fotini Kanouta; Theodora Psaltopoulou; Georgia N. Kassi (Elsevier, 2022)
SARS-CoV-2 vaccination is the most powerful and promising tool against the COVID-19 pandemic. Millions of people have been vaccinated worldwide. Recently, few cases of subacute thyroiditis following SARS-CoV-2 vaccination with various types of vaccine have been reported. We describe here a 36-year-old woman who presented with subacute thyroiditis 10 days after she had received her first dose of the SARS-CoV-2 mRNA vaccine Comirnaty (Pfizer/BioNTech); the condition receded but then recurred 10 days after she received her second dose. As vaccination programmes proceed, clinicians' attention and vigilance for such cases will be increased. Physicians need to know that subacute thyroiditis is a mild and self-limiting condition in the majority of cases. Last but not least, the benefits of vaccination against COVID-19 outweigh the side-effects reported so far.